A feasibility study on the application of a laccase-mediator system in stirred yoghurt at the pilot scale. (October 2016) - Mokoonlall, Aryama; Sykora, Laura; Pfannstiel, Jens; Nöbel, Stefan; Weiss, Jochen; Hinrichs, Jörg
Abstract: The crosslinking of milk proteins by laccases, often in the presence of a small phenolic mediator, has been demonstrated in model systems. In this study, the pilot scale application of a laccase-mediator system in stirred milk yoghurt in a post-processing step was assessed. Stirred skim milk yoghurt with 4.6% protein was treated with two laccase dosages (1 U/g or 3 U/g yoghurt) and vanillin concentrations (1 mM and 5 mM) at 20 °C for 24 h in a screening step. Mainly protein fragmentation was observed via SDS-PAGE due to laccase only while higher molecular weight oligomers were formed with laccase-vanillin. The storage modulus, viscosity and particle size were lower after laccase treatment, revealing a degradation in the gel structure. In a second step, laccase-vanillin combinations which resulted in the greatest structural modifications, namely 3 U laccase/g yoghurt or 5 mM vanillin, were applied to stirred skim and full milk yoghurt for sensory and structural analysis. Lower in-mouth viscosity and characteristic taste were evaluated for the laccase containing yoghurts, an effect exacerbated in the presence of vanillin. Additionally, lower structural parameters were observed, independent of vanillin. The storage modulus and apparent viscosity of the full milk yoghurt decreased by 18–29%. In line with this observation, a three- to four-fold higher concentration of smaller peptides was detected by fluorescence spectroscopy. Thus, the laccase-mediator system caused simultaneous protein crosslinking and fragmentation with an overall negative impact on the fermented milk gel structure and sensory perception. Graphical abstract: Highlights: Milk protein crosslinking by laccase and laccase-mediator systems is investigated. Competing oligomerisation and protein degradation is observed in stirred yoghurt. The rheological gel properties and particle size decrease after laccase treatment. In-mouth viscosity and characteristic taste perception is lower.